Vaccine- and natural infection-induced mechanisms that could modulate vaccine safety. (2020) - Kostoff, Ronald N.; Kanduc, Darja; Porter, Alan L.; Shoenfeld, Yehuda; Calina, Daniela; Briggs, Michael B.; Spandidos, Demetrios A.; Tsatsakis, Aristidis
Graphical abstract: Highlights: A future COVID-19 vaccine is being developed at unprecedented speed to augment immune system defenses. This paper presents myriad infection/vaccine-related mechanisms that could adversely impact vaccine effectiveness and safety. It is unclear how the present accelerated vaccine development program can address these longer-term impact vaccine safety issues. Abstract: A degraded/dysfunctional immune system appears to be the main determinant of serious/fatal reaction to viral infection (for COVID-19, SARS, and influenza alike). There are four major approaches being employed or considered presently to augment or strengthen the immune system, in order to reduce adverse effects of viral exposure. The three approaches that are focused mainly on augmenting the immune system are based on the concept that pandemics/outbreaks can be controlled/prevented while maintaining the immune-degrading lifestyles followed by much of the global population. The fourth approach is based on identifying and introducing measures aimed at strengthening the immune system intrinsically in order to minimize future pandemics/outbreaks. Specifically, the four measures are: 1) restricting exposure to virus; 2) providing reactive/tactical treatments to reduce viral load; 3) developing vaccines to prevent, or at least attenuate, the infection; 4) strengthening the immune system intrinsically, by a) identifying those factors that contribute to degrading the immune system, then eliminating/reducing them as comprehensively, thoroughly, and rapidly as possible, and b) replacing the eliminated factors with immune-strengthening factors. This paper focuses on vaccine safety. A future COVID-19 vaccine appears to be the treatment of choice at the national/international level. Vaccine development has been accelerated to achieve this goal in the relatively near-term, and questions have arisen whether vaccine safety has been/is being/will be compromised in pursuit of a shortened vaccine development time. There are myriad mechanisms related to vaccine-induced, and natural infection-induced, infections that could adversely impact vaccine effectiveness and safety. This paper summarizes many of those mechanisms.